Study the Semantic Contradiction in “Hezaro-Yekshabeno” and “Paribad” by Mohammad Ali Oloomi - Sara Tomzad; Parvin Tajbakhsh (مطالعات زبانی و بلاغی)
The contradiction is one of the techniques of art defamiliarization that highlights the context. This literary style is a basic feature in some fictional works. Story writers have been able to disassociate the distinction between fictional and real worlds and create a kind of uncertainty in the story. Conscious usage of this feature removes achieved results, thus makes reader surprised and doubtful. To reflect human situation in order to influence more on audience, the writer choosing contradiction method and reader, being involved, tries to identify and understand such contradictions. In order to create contradiction in “Hezaro-yekshabeno” and “Paribad”, Oloomi take advantageous of semantic contradiction. He uses paradoxical characterization, interference between real and fictional world, the intersection of genres, and repetition-based implication to show semantic contradiction in two mentioned stories. In this research, we aim to examine the types of semantic contradictions as a stylistic element in these stories by a descriptive - analytical method.